Assessment of Non-destructive Methods for Evaluating the Performance of Surface Treatments on Concrete - Sunday O. Nwaubani; Victor S. Gilayeneh (Journal of Building Materials and Structures)
Hydrophobic films are frequently applied to concrete structures to reduce water ingress and provide protection against weathering and chemical attacks. However, these waterproof coatings tend to deteriorate with time and require reapplication to maintain their effectiveness. Deciding when the retreatment should be applied and how to assess existing treated surfaces can sometimes be a challenging task for owners of concrete structures. Consequently, this paper presents findings on the assessment of absorption characteristics of surface-treated concrete using several techniques. Three non-destructive test methods were used to evaluate the efficacy of surface treatment under different curing conditions and with varying numbers of treatments. The methods employed were the initial surface absorption test, Karsten tube test and electrical conductivity test (wet method). The results show that the employed methods were all able to distinguish between treated and untreated surfaces. Treated samples exhibited better resistance to water absorption and electrical conductivity than untreated ones, and the absorption characteristics were found to be influenced by the number of treatments and curing regimes. All three test methods were effective in assessing surface treatment quality, with the Karsten tube test being the most practical for in-situ evaluation due to the simplicity of its setup.